PREVALENCE AND STRUCTURE OF DENTOALVEOLAR ANOMALIES AMONG STUDENTS OF DONETSK REGION - S.P. Yarova; О.A. Kobtseva; Yu.Yu. Yarov; K.V. Novikova; D.D. Kobtseva (Український стоматологічний альманах)
Harmonious facial aesthetics, proper bite, straight teeth are an integral part of individual psychological well-being and a modern person’s professional success. According to scientific studies, orthodontic pathology occupies third place in terms of incidence among dental diseases after dental caries and periodontal diseases. Being man-made polluted, the Donetsk region also has a high prevalence of dentoalveolar anomalies. In 7-15 year old children, the incidence rate is 68-90%.